Training and other predictors of personal protective equipment use in Australian grain farmers using pesticides. Issue 2 (17th August 2007) - MacFarlane, E; Chapman, A; Benke, G; Meaklim, J; Sim, M; McNeil, J
Abstract : Objectives: To investigate patterns of use of personal protective equipment (PPE) to reduce pesticide exposure in a sample of Australian farmers and also to assess the influence of possible predictive factors. Methods: A cross-sectional survey of 1102 farmers recruited through the Victorian Farmers Federation (VFF) was conducted. A written questionnaire was filled out by participants at VFF meetings attended by a visiting research assistant. Participants answered questions about frequency of pesticide use and PPE items they usually used when doing two different pesticide-related tasks, mixing and application, of each of four classes of pesticides. They also answered questions about personal characteristics, farm characteristics, farming activities, career and health. Results: Nearly all surveyed farmers had ever used pesticides, and over 87% had used Herbicides or Animal Health Products in the previous 12 months. Non-use of PPE was frequently reported, with up to 10–40% of farmers routinely using no PPE at all when using pesticides. Across all pesticide classes, PPE use was higher for pesticide mixing than for application. In multivariate analyses PPE use appeared to be most strongly associated with younger age and farm chemical training. Conclusions: PPE use across all pesticide classes was poor, indicating the possibility of clinically significant pesticide exposure in many farmers. Given that PPE use was found to be associated with farm chemical training, the authors suggest that training is likely to be an important intervention for reducing farmers' pesticide exposure. Poor uptake of farm chemical training by farmers and the aging farming workforce are causes for concern in the light of these findings.